Rediscovery, new island record, and clarification of the geographic distribution of oligodon perkinsi (Taylor, 1925) (squamata, colubridae), a poorly known endemic snake from the Palawan faunal region of western Philippines - Supsup, Christian E. (Animo Repository, 2020)
Snakes of the genus Oligodon Fitzinger, 1826 are rarely observed and infrequently collected in the Philippines. Here we report the rediscovery and first documentation of Oligodon perkinsi (Taylor, 1925) after nearly 60 years. Our observation extends the species distribution to Busuanga, an island located north of Culion (type locality) and on the western side of the archipelago. © The authors.